A quantitative study on quality of physical infrastructure, WASH practices, preschool education and safety in Anganwadi centers, government preschools and private preschools in Delhi - Zeba Tabassum; Kainat Khalid; Sumayya Neyazi; Ebtisham Ahmed (Discover Education)
Abstract The foundation of all learning depends upon early childhood experiences, which consist of the pre-schooling age of a child’s life, i.e., 3 to 6 years. So, preschools play a significant role in all learning. Enhanced cognitive, social, and language capabilities and even a higher level of school readiness can be achieved through the quality of preschool programs. Therefore, this study’s aim was to understand the quality of various modes of preschool, i.e., Anganwadi centers, government preschools, and private preschools, regarding their physical infrastructure, WASH practices, preschool education, and safety, which run in Delhi. A total of 45 preschools were taken, 15 from each mode, and a descriptive research design was used to compare the quality of the different modes. The findings show that government preschools and private preschools are working at good quality in terms of physical infrastructure, safety of the children, and classroom process. On the other hand, Anganwadi centers are working mostly at average quality in all variables. All three modes of preschool should extensively work on the WASH practices and preschool education, especially in curriculum transaction and a child-friendly environment, as they require substantial attention.